MODELING OF QUALITY IMPROVEMENT FACULTY MEMBERS IN EDUCATIONAL ORGANIZATIONS HIGHER EDUCATION - N. V. Sergeeva (Модернизация, инновация, развитие, 2015)
The transition to a two-tier system of education, the introduction of the federal state educational standards of higher education, the requirements of the single European educational space are fundamentally changing the role of faculty in the professional educational organizations of higher education as a simple translator subject knowledge.